Inflation and the macro economic problems in Nigeria: an islamic perspective (2013)
One of the most crucial macroeconomic problems for most countries of the world is inflation. Although many countries particularly the developed countries experience rise in prices, the extent of the rise is so small that may go unnoticed by their people. However, this is not the case in Nigeria where it is double digit and with no signs of slowing down. In this paper, inflation in the conventional economy is discussed in the light of Islamic economy. It also examines if Shari'ah allows protection against inflation for the lender in a financial transaction. The effects of inflation rates on interest rates in Nigeria and how they can be controlled using Islamic finance are also examined. Islam supports zero rate of interest. However, it is indifferent to zero inflation inasmuch as it is not caused by human factors. If full employment prevails, the rate of inflation will be zero. The paper shows that inflation is allowed to some extent while indexation is not allowed because of injustice. An Islamic economy is not prone to a high rate of inflation due to some built-in stabilizers. We note some characteristics of Islamic finance that can prevent inflation from occurring or at the least can reduce the negative effects of inflation in an Islamic economy.